Era das distopias: pessimismo e catástrofe na narrativa de ficção - França, Rafael de Abreu Carneiro (2024)
This master's thesis sought to study classic dystopian fiction from the first half of the 20th century, aiming to understand the historical moment in which they were produced to understand how important civilizational issues of the time are still present in the 21st century. Based on the relationship between art and politics, similarities with society at the time in which they were written were highlighted. The dystopian genre has modern roots in the 19th century, but became popular in the middle of the last century through classics such as Brave New World and 1984. The relationship between its commercial rise through the mass cultural industry in the 20th century and the civilizing moment in which we live in modernity was evaluated to discover the overlap between the functioning of modern capitalism, political thought and dystopian fiction. Issues such as traditional and critical thinking, rationalization, mass cultural industry, industrial society, Fordism, Taylorism, romanticism and capitalist modernity were investigated through a theoretical repertoire that includes the Critical Theory of Society – especially the thinkers of the so-called “Frankfurt School” such as Theodor Adorno, Max Horkheimer and Herbert Marcuse – and the concept of control society defined by Giles Deleuze based on Michel Foucault's thoughts on disciplinary society, also studied here, to then arrive at the analysis of classic dystopias and conclusions regarding them